2021
DOI: 10.2174/1385272825999210104222338
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Synthesis, Reactions and Biological Properties of Seven Membered Heterocyclic Compounds: Azepine, Azepane, Azepinone

Abstract: Seven membered heterocyclic Azepine and its derivatives have great pharmacological and therapeutic implications. In this review, the literature of the last fifty years has been exploited for the synthesis, reaction, and biological properties of these seven-member heterocyclic compounds. Most of the mechanisms involved the ring expansion of either five or six-membered compounds using various methods such as thermally, photo-chemically, and microwave irradiation. The systematically designed schemes involve the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 278 publications
0
39
0
Order By: Relevance
“…1). 3 To date, considerable protocols have been reported for the asymmetric synthesis of these optical pure skeletons, 1,4 including an asymmetric tandem allylic vinylation/amination reaction, 5a enantioselective addition of organometallic reagents, 5b alkynylation, 5c Mannich addition, 5d,e aza-Reformatsky reactions to the dibenzo-fused azepines, 5f and so on. Among them, the catalytic asymmetric hydrogenation of corresponding dibenzo-fused azepines represents one of the most prominent approaches to obtain such chiral molecules.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1). 3 To date, considerable protocols have been reported for the asymmetric synthesis of these optical pure skeletons, 1,4 including an asymmetric tandem allylic vinylation/amination reaction, 5a enantioselective addition of organometallic reagents, 5b alkynylation, 5c Mannich addition, 5d,e aza-Reformatsky reactions to the dibenzo-fused azepines, 5f and so on. Among them, the catalytic asymmetric hydrogenation of corresponding dibenzo-fused azepines represents one of the most prominent approaches to obtain such chiral molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the catalytic asymmetric hydrogenation of corresponding dibenzo-fused azepines represents one of the most prominent approaches to obtain such chiral molecules. 4,6 In 2011, Zhou and co-workers reported that the iridium diphosphine complexes are efficient catalysts for the asymmetric hydrogenation of dibenzo[b, f ] [1,4]-oxazepines (up to 94% ee) in the presence of morpholine-HCl, 7a and later on, a similar chiral iridium catalyst was applied to the asymmetric hydrogenation of dibenzo[b, f ] [1,4]-thiazepines (up to 96% ee) in the presence of iodine (Scheme 1a). 7b In 2013, Pd complexes of chiral diphosphines proved to be effective catalysts for the asymmetric hydrogenation of dibenzo[b, f ] [1,4]-thiazepines (up to 94% ee) with the addition of a Brønsted acid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both 1,4-benzodiazepine and 1,4-benzoxazepine scaffolds containing fused heterocycles are ubiquitous in natural products, bioactive molecules, and pharmaceuticals (Scheme a) . Indeed, several of these seven-membered heterocycles have been identified as selective inhibitors of mitochondrial F 1 F 0 ATP hydrolase ( I ), as well as antihistaminic and antianaphylactic agents (tarpane, II ) .…”
mentioning
confidence: 99%